Vision to Action report for Mbire and Murehwa, Zimbabwe - Sibanda, Telma; Choruma, Dennis J.; Baudron, Frederic; Voss, Rachel C.; Chimonyo, Vimbayi G.P. (CGIAR, 2024)
Developing a vision-to-action plan is essential for guiding the transition to agroecology in Mbire and Murehwa. This plan, grounded in agroecological principles, aims to minimize conflicts and promote participation, equity, and the integration of scientific and local knowledge throughout the engagement process. The key objectives included articulating a vision, identifying behavior changes, understanding their drivers, co-designing transition pathways, and formulating action plans and Monitoring, Evaluation, and Learning (MEL) systems for Agroecological Living Landscapes (ALLs) to track progress effectively. The methodology emphasizes inclusiveness, diversity, and representativeness, ensuring genuine stakeholder engagement. Workshops involved group discussions among different demographic segments to capture varied perspectives, fostering inclusive decision-making. The transition towards sustainable agroecology in Mbire and Murehwa requires key behavior changes among farmers and communiies. These include adopting improved agricultural practices, enhancing knowledge and skills through continuous learning and training, increasing women's participation in leadership and income-generating activities, and improving market access. Additionally, crucial elements include enhancing environmental stewardship, coexisting with wildlife, promoting social cohesion, and reducing gender-based violence. Shifting towards entrepreneurial mindsets by exploring new business models and value addition opportunities is also essential. These changes aim to build resilient, sustainable, and equitable local food systems, thereby improving agricultural productivity and overall community well-being. Findings were integrated with the Local Indicators Selection Process (LISP) to develop a comprehensive monitoring and evaluation framework. This approach ensures that selected indicators reflect local needs and priorities, supporting robust monitoring, evaluation, and adaptive management. Ultimately, this process aims to cultivate a shared understanding, community engagement, and coherent progress toward building sustainable agroecological systems in Zimbabwe.